Iskandar.my: framework of mobile augmented reality travel app - Mohd, Nur Shuhadah; Abdul Aziz, Maimunah; Ismail, Hairul Nizam (Springer Nature, 2022)
In today’s world, Mobile Augmented Reality (AR) technology has been increasingly adopted by tourism industrial players in product development mainly due to the technology’s ability in improving tourists’ destination interaction through dynamic digital engagement. Mobile Augmented Reality (MAR) travel app, such as ‘Iskandar.my’, is seen capable to attract users’ excitement during travel by augmenting relevant travel-related information media, at the same time still leaving some space for tourist appreciation of the real environment. This research explores the technological framework of ‘Iskandar.my’ MAR travel apps and elaborates on the service dimension and design dimension of the app. These dimensions of the technological framework would explain the value co-creation experienced by users from the digital engagement and enlighten the possibility of being the antecedent of users’ travel satisfaction.